2020
DOI: 10.1136/bmjdrc-2020-001575
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is associated with elevated urinary pyrrole markers of γ-diketones known to cause axonal neuropathy

Abstract: IntroductionProgressive distal symmetrical axonal neuropathy, a complication of diabetes mellitus (DM), has an unknown cause. Normal physiological metabolism and diabetic dysmetabolism are associated with the generation of γ-diketones. γ-Diketones form pyrroles with protein amines, notably with axonal proteins required for the maintenance of nerve fiber integrity, especially elongate, large-diameter peripheral nerve fibers innervating the extremities. We tested the hypothesis that neuropathy-associated γ-diket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Figure 1 shows that we drew on a population ( n = 534) of 60–79 year‐old Chinese persons who resided in the Luohu district of Shenzhen City, Guangdong Province, China; these individuals had previously participated in a published case–control study. 11 Eight persons with abnormal kidney function, eight individuals aged >80 years, and two individuals with extreme glucose levels (HbA1c > 15%) were excluded. Among the 516 remaining individuals, 258 with elevated glucose indices (glycated hemoglobin HbA1c ≥ 6.5% and FBG ≥ 7.0 mM) were shortlisted for assessment of DSPN symptom and resting heart rates.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows that we drew on a population ( n = 534) of 60–79 year‐old Chinese persons who resided in the Luohu district of Shenzhen City, Guangdong Province, China; these individuals had previously participated in a published case–control study. 11 Eight persons with abnormal kidney function, eight individuals aged >80 years, and two individuals with extreme glucose levels (HbA1c > 15%) were excluded. Among the 516 remaining individuals, 258 with elevated glucose indices (glycated hemoglobin HbA1c ≥ 6.5% and FBG ≥ 7.0 mM) were shortlisted for assessment of DSPN symptom and resting heart rates.…”
Section: Methodsmentioning
confidence: 99%
“…Fluctuations typical of a circadian rhythm were not observed for 2,5-hexanedione in blood or urine. Excretion of 2,5-hexanedione was inversely related to age among Chinese subjects [ 99 ], while a comparison of two independent studies suggested that levels of urinary pyrroles were markedly higher in older persons [ 101 , 102 ].…”
Section: Endogenous 25-hexanedione and Associated Pyrrolesmentioning
confidence: 99%
“…We assayed the urinary concentration of γ-diketone pyrroles in age- and gender-matched elderly (60–84 years) Chinese persons with and without ( n = 267/group) indicators of diabetes mellitus. Subjects were drawn from a community of 9411 adults aged ≥ 60 years in the city of Shenzhen, Guangdong, China [ 102 ]. Subjects with diabetes mellitus relative to healthy controls had significantly higher levels of fasting blood glucose, glycated hemoglobin A1c, urinary ketone bodies, and urinary γ-diketone pyrroles.…”
Section: Relationship To Neuropathies Of Endogenous Originmentioning
confidence: 99%
See 2 more Smart Citations